1996
DOI: 10.1163/156853996x00279
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Male and Female Zebra Finches Treated With an Estrogen Synthesis Inhibitor as Nestlings

Abstract: In order to test hypotheses about the organizational role of early estrogen in the sexual differentiation of behavior in zebra finches (Taeniopygia guttata), newly hatched birds were given one of three treatments: (1) daily injection with an aromatase inhibitor (fadrozole hydrochloride) for the first week; (2) the same treatment for the first two weeks; (3) daily injection of the vehicle for one or two weeks. As adults, birds were implanted with testosterone propionate and underwent a three-phase testing proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In laboratory colonies of zebra finches, it is not uncommon to see an occasional same-sex pair among nonexperimental birds, especially among females with limited access to males (Adkins-Regan et al 1996), which would explain the low, but nonzero, interest in same-sex birds seen in the control groups here. The significantly elevated incidence of this behaviour in the male-removal groups is none the less striking.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In laboratory colonies of zebra finches, it is not uncommon to see an occasional same-sex pair among nonexperimental birds, especially among females with limited access to males (Adkins-Regan et al 1996), which would explain the low, but nonzero, interest in same-sex birds seen in the control groups here. The significantly elevated incidence of this behaviour in the male-removal groups is none the less striking.…”
Section: Discussionmentioning
confidence: 70%
“…Thus they could hear but not see or contact birds of the opposite sex. Unisex housing at this age does not by itself alter sexual partner preference in either sex (Adkins-Regan et al 1996).…”
Section: Nestlings and Juvenilesmentioning
confidence: 77%
“…Partner preference is also known to be sexually differentiated in other avian species and in mammals, and a number of studies have demonstrated that perinatal hormones, including estrogens, have organizing effects on sex-typical partner preferences in adulthood (Adkins-Regan, Mansukhani, Seiwert, & Thompson, 1994; Adkins-Regan, Yang, & Mansukhani, 1996; Bakker, Van Ophemert, & Slob, 1993; Baum, Erskine, Kornberg, & Weaver, 1990; Brand, Kroonen, Mos, & Slob, 1991; Brand & Slob, 1991). The present experiment clearly indicates that embryonic estrogens have important effects on the organization of this behavioral response in quail, and this species may therefore constitute an excellent model to study the neural mechanisms underlying this important aspect of sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Little experimental work on this topic has been made in animal models, but in one species of songbirds, the zebra finch (T. guttata), which is known to form long-term sociosexual bonds, research in the Adkins-Regan laboratory has clearly demonstrated that young females treated with estrogens during the first 2 weeks post-hatch will prefer other females over males in two-choice proximity tests, and will pair with females in mixed-sex aviaries where they have ample choice of partners [192][193][194] (see Refs 193,195 for discussion of a few puzzling aspects of this research, including the fact that unexpectedly treatment with an aromatase inhibitor produces a similar change in partner preference). Little experimental work on this topic has been made in animal models, but in one species of songbirds, the zebra finch (T. guttata), which is known to form long-term sociosexual bonds, research in the Adkins-Regan laboratory has clearly demonstrated that young females treated with estrogens during the first 2 weeks post-hatch will prefer other females over males in two-choice proximity tests, and will pair with females in mixed-sex aviaries where they have ample choice of partners [192][193][194] (see Refs 193,195 for discussion of a few puzzling aspects of this research, including the fact that unexpectedly treatment with an aromatase inhibitor produces a similar change in partner preference).…”
Section: Interactions Between Biological (Hormones Genes) and Socialmentioning
confidence: 99%